Analysis of Factors Affecting Mobile Banking Customer Loyalty in the Greater Jakarta Area - Pualam Wahyu Ratiasasadara; Ferryal Abadi (Journal Research of Social Science, Economics, and Management, 2026)
The rapid growth of mobile banking services requires banks to better understand the factors that shape customer loyalty in an increasingly competitive digital environment. This study aims to analyze the factors influencing customer loyalty in mobile banking services in the Jabodetabek area by considering perceived security, customer convenience, service quality, and perceived value, with customer satisfaction as a mediating variable. This research employed a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 451 mobile banking users and analyzed using SEM-PLS approach. The results indicate that customer convenience, service quality, and perceived value have a positive and significant effect on customer loyalty. Perceived security does not have a direct effect on customer loyalty, but it has a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on customer loyalty and mediates the relationship between perceived security, customer convenience, service quality, and customer loyalty. However, customer satisfaction does not mediate the relationship between perceived value and customer loyalty. This study provides practical implications for banking institutions in developing strategies to enhance mobile banking customer loyalty through improved convenience, service quality, and overall customer experience management. Suggestions for future research include adding several variables, particularly trust, and expanding the scope of the study.